ANALISIS HISTORIS TENTANG SUFISME AL-GHAZĀLĪ - Salahuddin Salahuddin (State Institute of Islamic Studies (IAIN) Palu, 2010)
Al-Gazālī is views as a figure who succeeded to reconciled between the Shari'a with Sufism, and it was he who succeeded to make the teaching of sufism be accepted by the fiqh ulamahis (scholars of Fiqh). Sufism is the final path which he chose before which he intensely studied the sensory sciences, theology, and philosophy. It was in Sufism, according to him, that he found the true knowledge which comes from the Creator.Kata Kunci: analisis sufisme. Al-Ghazali, syariat, tasawuf